(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify: 1- The degree of psychological resilience of educational counselors. 2- The degree of job performance of educational counselors 3- the relationship between psychological resilience and job performance of educational counselors. To achieve the objectives of the research, the researcher adopted the measure of psychological resilience prepared by (Al-Zuhairi, 2012) consisting of (49) paragraphs and five alternatives (always apply to me, apply to me). Mostly, applies to me sometimes, applies to me rarely, never applies to me), and the researcher prepared a job performance scale consisting of (30) paragraphs and five alternatives (always apply to me, apply to me often, apply to me sometimes, apply to me rarely, do not apply Ali never), and after applying the two scales to the research sample consisting of (100) male and female counsellors, the results showed that the degree of psychological flexibility of the counselors was high (165.133) and the degree of job performance was also high (115.122). As for the relationship between the two variables, it is a strong and positive relationship.